Radiopaque Nanorobots as Magnetically Navigable Contrast Agents for Localized In Vivo Imaging of the Gastrointestinal Tract - Oral, Cagatay M; Ussia, Martina; Urso, Mario; Salat, Jiri; Novobilsky, Adam; Stefanik, Michal; Ruzek, Daniel; Pumera, Martin (Advanced healthcare materials, 2023)
Magnetic nanorobots offer wireless navigation capability in hard-to-reach areas of the human body for targeted therapy and diagnosis. Though in vivo imaging is required for guidance of the magnetic nanorobots toward the target areas, most of the imaging techniques are inadequate to reveal the potential locomotion routes. This work proposes the use of radiopaque magnetic nanorobots along with microcomputed tomography (microCT) for localized in vivo imaging applications. The nanorobots consist of a contrast agent, barium sulfate (BaSO4 ), magnetized by the decoration of magnetite (Fe3 O4 ) particles. The magnetic features lead to actuation under rotating magnetic fields and enable precise navigation in a microfluidic channel used to simulate confined spaces of the body. In this channel, the intrinsic radiopacity of the nanorobots also provides the possibility to reveal the internal structures by X-ray contrast. Furthermore, in vitro analysis indicates nontoxicity of the nanorobots. In vivo experiments demonstrate localization of the nanorobots in a specific part of the gastrointestinal (GI) tract upon the influence of the magnetic field, indicating the efficient control even in the presence of natural peristaltic movements. The nanorobots reported here highlight that smart nanorobotic contrast agents can improve the current imaging-based diagnosis techniques by providing untethered controllability in vivo.
Keywords: magnetic actuation; X-Ray Microtomography; gastrointestinální trakt; computed tomography; medical imaging; gastrointestinal tract; rentgenová mikrotomografie; nanomotors; Gastrointestinal Tract; lidé; nanoswimmers; tracking; magnetismus; Magnetics; Contrast Media; kontrastní látky; Humans